Lower prevalence of hepatic fibrosis in low viremic hepatitis B patients with fluctuating HBV DNA levels - Faisal M Sanai; Ahmad H Alhouthali; Hamdan S Alghamdi; Feras Badriq; Eisa A Sanai; Mohammed K Mujalled; Waleed Khayyat; Motaz S Attar; Basil S Bagadeem; Alaa M Meer; Waleed Alshumrani; Khalid Albeladi; et al. (The Saudi Journal of Gastroenterology, 2022)
Background: In chronic hepatitis B virus (HBV) patients, fluctuations in HBV DNA serve as a “gray area” and impede the accurate identification of inactive carriers. We aimed to assess if such fluctuations impact the presence of significant hepatic fibrosis (Metavir F2-4) in chronic HBV patients. Methods: Consecutive, untreated HBeAg-negative carriers (n = 234) with fluctuating HBV DNA (n = 73) above or below a level of 2000 IU/mL were included and compared to those without fluctuations (n = 161). Patients without fluctuating HBV DNA were further analyzed based on those with persistently low (<2,000 IU/mL, n = 137) and higher HBV DNA (2,000–20,000 IU/mL, n = 24). Hepatic fibrosis (assessed by transient elastography) was correlated with virologic and biochemical profiles. Results: The mean age of the overall cohort was 47.8 ± 11.1 years, of whom 107 (45.7%) were male. During a median of 60 months (interquartile range [IQR] 34–82) of follow-up, 73 (31.2%) patients had a mean of 1.6 ± 0.9 fluctuations in HBV DNA. The median time to the first fluctuation was at 14.5 (IQR 5.0–33.7) months. Patients with fluctuating viremia had higher log10 qHBsAg (3.1 ± 0.8 vs. 2.7 ± 1.0, P = 0.022) and HBV DNA (3.4 ± 0.5 vs. 2.7 ± 0.8, P < 0.001) compared to those without fluctuations. Patients with fluctuant viremia were less likely to have F2-4 fibrosis (8.2%) compared to those without fluctuant viremia (18.2%, odds ratio [OR]: 0.407, 95% confidence interval [CI]: 0.161–1.030; P = 0.052). Males tended to have less fluctuation constituting 37.0% of patients with fluctuating HBV DNA (P = 0.071). Fluctuations occurred more frequently in those with predominantly higher HBV DNA levels (26.0%) compared to those without fluctuations (14.9%; P = 0.030). Conclusions: Fluctuating HBV DNA levels occur frequently but are not associated with significant fibrosis. Minor fluctuations in HBV DNA levels are unlikely to be of clinical relevance.